Evaluation of the in vitro permeation parameters of topical ketoprofen and lidocaine hydrochloride from transdermal Pentravan® products through human skin - Adamiak-Giera, Urszula; Nowak, Anna; Duchnik, Wiktoria; Ossowicz-Rupniewska, Paula; Czerkawska, Anna; Machoy-Mokrzyńska, Anna; Sulikowski, Tadeusz; Kucharski, Łukasz; Białecka, Marta; Klimowicz, Adam; Białecka, Monika (Frontiers in Pharmacology, 2023)
In the treatment of pain, especially chronic pain, the rule of multimodal therapy applies, based on various painkillers mechanisms of action. The aim of the conducted study was to evaluate the in vitro penetration of ketoprofen (KET) and lidocaine hydrochloride (LH) through the human skin from a vehicle with transdermal properties. The results obtained with the use of the Franz chamber showed statistically significantly higher penetration of KET from the transdermal vehicle as compared to commercial preparations. It was also shown that the addition of LH to the transdermal vehicle did not change the amount of KET permeated. The study also compared the penetration of KET and LH by adding various excipients to the transdermal vehicle. Comparing the cumulative mass of KET that penetrated after the 24-hour study, it was observed that the significantly highest permeation was found for the vehicle containing additionally Tinctura capsici, then for that containing camphor and ethanol, and the vehicle containing menthol and ethanol as compared to that containing Pentravan® alone. A similar tendency was observed in the case of LH, where the addition of Tinctura capsici, menthol and camphor led to a statistically significant higher penetration. Adding certain drugs such as KET and LH to Pentravan®, and substances such as menthol, camphor or capsaicin, can be an interesting alternative to administered enteral drugs especially in the group of patients with multiple diseases and polypragmasy.